HAK WARIS ANAK LUAR NIKAH PERSPEKTIF KEADILAN HUKUM HANS KELSEN DAN WARIS SUNNI (STUDI PMK NOMOR 46/PUU-VIII/2010) - Tirmidzi, Ahmad; Mahmudi, Zaenul; Toriquddin, Moh. (JURNAL AL-IJTIMAIYYAH, 2022)
Abstract: The constitutional court's decision No. 46/PUU-VIII/2010 was passed in response to the judicial review submissions of Mochicha Mochtar and Iqbal Ramdan who felt that their constitutional rights were hindered by the law, namely article 43 paragraph (1) of the Law. No. 1 of 1974 on Marriage. Under the article, every children born out of wedlock does not have a civil law relationship with his father. The condition of children born out of wedlock can be analogous like a person who is exposed to sap without eating the fruit, meaning that the children born out of wedlock is not the actor of violations of legal action, but he is exposed to the burden of law for violations committed by both parents. Though every child is born without carrying the burden of sins committed by both parents and remains in a fitrah. The constitutional court's decision aims to uphold justice for the inheritance rights of children born out of wedlock who are considered hindered by one of marriage law articles in Indonesia. The purpose of this study is to analyze the principle of justice related to the civil rights of children born out of wedlock in Constitutional Court Decision No. 46 / PUU-VIII / 2010 perspective of legal justice Hans Kelsen and coherence with Sunni inheritance law. This research is normative-descriptive research with library research methods. The constitutional court's ruling has a coherence with the opinion of Abu Hasan Al-Mawardi who said an illegitimate child can be descended of a man as his father after a blood relationship can be proven. After being analyzed with the legal justice of Hans Kelsen, the Constitutional Court's verdict has contained the value of justice. So that parties who have interests related to the civil rights of children born out of wedlock must be obedient to the content of the ruling.Keywords: Inheritance of Children Born Out of Wedlock; Sunni Inheritance Law; Hans Kelsen's Legal Justice.       Abstrak: Putusan MK No. 46/PUU-VIII/2010 disahkan sebagai respon atas pengajuan judicial review Mochicha Mochtar dan Iqbal Ramdan yang merasa hak konstitusionalnya dihalangi oleh undang-undang yaitu Pasal 43 ayat (1) Undang-undang No. 1 Tahun 1974 tentang Perkawinan. Berdasarkan pasal tersebut setiap anak luar nikah tidak mempunyai hubungan keperdataan dengan ayahnya. Posisi anak dapat dianalogikan seperti orang yang terkena getah tanpa memakan buahnya, artinya anak yang terlahir di luar nikah bukan pelaku pelanggaran tindakan hukum, namun ia terkena beban hukum atas pelanggaran yang dilakukan kedua orang tuanya. Padahal setiap anak terlahir tanpa membawa beban dosa yang diperbuat oleh kedua orang tuanya dan tetap dalam keadaan fitrah. Putusan MK tersebut bertujuan menegakkan keadilan atas hak-hak keperdataan anak luar nikah yang dinilai terhalangi oleh salah satu pasal dalam undang-undang perkawinan di Indonesia. Adapun tujuan dari penelitian ini adalah menganalisi prinsip keadilan terkait hak waris anak luar nikah dalam Putusan MK No. 46/PUU-VIII/2010 perspektif keadilan hukum Hans Kelsen. Penelitian ini merupakan penelitian normatif-deskriptif dengan metode library research. Putusan MK tersebut mempunyai koherensi dengan pendapat Abu Hasan Al-Mawardi yang mengutarakan anak luar nikah dapat nasab dengan laki-laki sebagai ayahnya setelah hubungan darah dapat dibuktikan. Setelah dianalisis dengan keadilan hukum Hans Kelsen, Putusan MK tersebut telah memuat nilai keadilan. Sehingga pihak yang mempunyai kepentingan terkait hak keperdataan anak luar nikah harus bersikap patuh terhadap isi putusan tersebut.Kata Kunci: Waris Anak Luar Nikah; Hukum Waris Sunni; Keadilan Hukum Hans Kelsen.